Indigenous Intangible Cultural Heritage: Towards an Indigenous Approach to Canadian Heritage Management and Planning - Stevens, Julia (University of Waterloo, 2017)
Canada’s ‘official’ heritage is overwhelmingly comprised of designated buildings, monuments, landscapes, and streetscapes that reflect notable architectural styles or historic character, celebrated places, and key agents in Canada’s historical narrative. Heritage management and planning regimes in Canada, and western societies, utilize a well-established material, or tangible, understanding of heritage recognition. Indigenous forms of heritage, which are often manifested as non-material, or intangible cultural heritage (ICH), do not readily fit within western paradigms of heritage. As a result, Indigenous ICH does not receive the same attention or support as western material heritage and remains underrepresented within the current heritage management system. This exploratory thesis seeks to examine and place the Canadian heritage management and planning regime as a colonial legacy. A review of the literature suggests that although the academic body of Indigenous planning theory and critical research is growing, there is a notable gap in understanding how heritage planning can be effectively decolonized. Further, the literature indicates that Western and Indigenous perspectives of ‘heritage’ differ significantly, however little research has been conducted to address how heritage planning systems can be re-imagined to include Indigenous ICH and worldviews. Utilizing a qualitative research methodology, twenty-four Indigenous and non-Indigenous heritage practitioners and planners from across Canada were interviewed. Additionally, provincial and federal heritage legislation and supporting policy documents were analysed in order to ascertain how Indigenous heritage is currently recognized within Canada’s material-focused heritage planning regime. The findings that emerged from this thesis research suggest: 1) Heritage planning and management in Canada continues to be overwhelmingly material focused and displays a lack of understanding of ICH; 2) The diffusion of responsibilities between federal, provincial, and municipal governments on Indigenous and heritage related issues poses challenges of governance, legislation, policy, and programming; 3) The influences of colonialism have left a legacy of distrust between Indigenous communities and settler society, leading to reluctance by some Indigenous communities to share traditional knowledge and heritage with non-community members; 4) Many Indigenous communities and governments face pressing social concerns; as a result, heritage and cultural programming is often a lower priority for some communities; 5) Increased understanding of Indigenous intangible cultural heritage in Canadian historical narratives can potentially support the process of reconciliation, increase cultural knowledge, capacity, and resiliency in Indigenous communities, and encourage a stronger Indigenous cultural presence and understanding in Canadian society. Emergent recommendations include: 1) Increase knowledge and awareness of Indigenous history and worldviews in Canadian planning schools; 2) Amend heritage legislation and policy to include Indigenous ICH; 3) Support avenues for Indigenous-led community-based cultural heritage programming; and 4) Encourage further research in Indigenous ICH and heritage planning field. This research is significant because it provides an exploratory look into how Indigenous ICH is currently considered in Canadian heritage planning and provides practical and theoretical recommendations for further studies into the benefits of recognizing ICH in an Indigenous post-colonial context, to arguably support a paradigm shift in what we, as Canadians, value as ‘heritage’.
Keywords: Indigenous Planning; Canadian Heritage Planning; Intangible Cultural Heritage; Indigenous Intangible Cultural Heritage